The Development of Educational Leadership and Change Management in the Era of Educational Innovation - Rookit, Wilailuck; Saengsrirueang, Nisarat; Inphusa, Siwakorn; Hapa, Yingsan; Wisitthapanyo, Phra Maha Phisit (Journal of Buddhist Education and Research (JBER), 2025)
These Educational leaders play a crucial role in driving educational organizations toward their objectives, particularly in the present era of rapid technological and innovative change. These leaders must possess diverse capabilities, encompassing vision creation, personnel development, and the implementation of innovation in educational management. They must also inspire, foster a learning culture, and promote collaborative work environments. Educational leadership comprises essential components including vision and strategy, change management capability, technology and innovation utilization, human resource management, ethics and morality, and community relationship building. Leaders must demonstrate key characteristics in strategic decision-making, communication, and innovative leadership approaches. Leadership development can be achieved through multiple channels, including professional training, mentorship learning, practical experience, and network building. Leaders must fulfill significant roles as vision creators, change managers, innovation developers, collaboration builders, and ethical role models to guide educational organizations toward success in the digital era.